The Role of Traffic Society Education in Reducing Traffic Accidents in the Manado Police Legal Area - Jeremy Salomo Luther Rawis (Advances in Police Science Research Journal, 2021)
Traffic accidents have become a problem that often occurs in the city of Manado, starting from the large population growth that causes the full number of road users. From this, people's ways of thinking and acting are different regarding traffic rules, many people's ways of thinking are still wrong, causing traffic accidents. In preventing and reducing this, the traffic unit prioritizes preventive efforts, namely through the Traffic Education Office, which aims to convey education about traffic to the public so that the public knows and understands good and orderly traffic procedures. In this thesis the author uses the theory of Management Functions, George R. Terry (5M), Communication Theory, Theory of Force Field Analysis and the concept of Social Education then as an analytical tool to discuss research findings and problems. This research uses a qualitative approach and the type of research is field research. The research focus is on the Traffic Unit Dikyasa Unit at the Manado Police with the community in Manado City as a source of document data, then the validity of the data is proven by data triangulation. Data analysis techniques in the form of data reduction, data presentation and drawing conclusions. The results of the study found that the number of traffic accidents in Manado City was still relatively high. The efforts of the Dikyasa Unit in preventing traffic accidents in the community were analyzed using management theory, communication theory, ffa theory and the concept of Dikmas Traffic. There are several supporting and inhibiting factors that affect the implementation of the Social Education Education. Based on the research results, various efforts have been carried out to prevent traffic violations. The author suggests reinforcing communication to the community, adding personnel, and adding infrastructure to support the activities of the Traffic Education Office in order to encourage community compliance to comply with the applicable rules.